Pengaruh Pendekatan Saintifik Berbantuan Metode Mind Mapping Terhadap Keterampilan Menulis Siswa Kelas VII SMPS Nidhomiyyah - Erina Yonanda Putri; Wuryaningrum, Rusdhianti; Pornomo, Bambang Edi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Jember, 2025)
Writing is the most complex language skill. In learning, writing is defined as the highest skill after listening, speaking, and reading skills. One of the competencies in the field of writing is presented in the material of writing news texts. To achieve this competency, an appropriate learning approach and technique are needed. Therefore, a scientific approach assisted by the mind mapping method was chosen. The scientific approach and the mind mapping method have a complementary relationship in the student-centered learning process. The scientific approach directs students to think logically and systematically through five stages, namely: observing, asking, collecting information, reasoning, and communicating. Meanwhile, the mind mapping method functions as an effective visual aid to organize ideas and information obtained during the scientific process. This study is an experimental study, which measures the significance of the difference between variable X (the experimental class that applies the scientific approach with the mind mapping method) and variable Y (the control class with the conventional model). The results of the t-test calculation show a significance of 0.035. In accordance with the decision-making guidelines, namely if the significance value is <0.05, then the alternative hypothesis (Ha) which states that there is a significant difference in the influence of the application of the scientific approach assisted by the mind mapping method on the news writing skills of class VII students at SMPS Nidhomiyyah is accepted. Based on the results of the study, it can be concluded that the application of the scientific approach assisted by the mind mapping method can improve students' ability to write news texts.